The literature book - Canton, James (New York, New York : DK Publishing, 2016)
Examines "the greatest works of world literature, from the Iliad to Don Quixote to The Great Gatsby. Around 100 ... articles explore landmark novels, short stories, plays, and poetry that reinvented the art of writing in their time, whether Ancient Greece, post-classical Europe, or modern-day Korea"--Amazon.com.
Includes bibliographical references and index.
Keywords: Criticism, interpretation, etc